A community-based energy bank for electricity generation using renewable fuels: A case of rural community in Tak Province, Thailand - Kanta, Teerasin; Jesdapipat, Sitanon; Maneechot, Pisit (Community and Social Development Journal, 2018)
By 2040 the desire for using energy of the world’s people will increase by 30% of the present. (Siamintelligence, 2011). Hence, countries move to explore and promote alternative energy, including renewable options to pamper ever-rising demand for energy. Yet leaders of renewable power developers remain mostly in developed countries as Table 1 thanks mainly to resource endowment and development capacity. Only China and India from developing country appear on the list, indicating that there might be some challenges that need to be overcome in promoting renewable energy. The same challenges may exist in Thailand. Being an oil dependent country, Thailand imports about 80% of the energy supply (Department of Alternative Energy Development and Efficiency, n.d.), fossil fuels specifically, thus making the Thai economy vulnerable to the price and supply volatility of the world oil markets (BP, 2012). Also, being a small importing country, Thailand has had gambled its economic development and social betterment on oil imports. Though Thailand has not been able to disassociate itself from fossil fuels, energy policies have been focusing on both supply and demand sides to reduce this dependency.